2023
DOI: 10.1037/drm0000237
|View full text |Cite
|
Sign up to set email alerts
|

Typical dreams of Chinese elderly people during COVID-19 pandemic.

Abstract: This study aimed at investigating the dream themes of Chinese elderly people during COVID-19 and its relationship with death anxiety. In this study, 264 participants from four cities in different regions of China were interviewed through one-on-one interviews. Nielsen's Typical Dream Questionnaire (TDQ) and Death Anxiety Scale (DAS) were also administered. The dream recall rate of the elderly was 48.48%; there were differences in TDQ35 and TDQ1 between the experimental group (EG) and control group (CG); the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Several studies have found that pandemic dreams are characterized by prevalent and intense negative emotions such as fear, anxiety, panic, anguish, and so forth (Avci, 2022;Giovanardi et al, 2022;Iorio et al, 2020;Marogna et al, 2021;Yang et al, 2023), which is consistent with the present study. Most dreams reported by frontline HCW involve unpleasant feelings such as anxiety, fear, or loneliness.…”
Section: Negative Emotionssupporting
confidence: 93%
See 4 more Smart Citations
“…Several studies have found that pandemic dreams are characterized by prevalent and intense negative emotions such as fear, anxiety, panic, anguish, and so forth (Avci, 2022;Giovanardi et al, 2022;Iorio et al, 2020;Marogna et al, 2021;Yang et al, 2023), which is consistent with the present study. Most dreams reported by frontline HCW involve unpleasant feelings such as anxiety, fear, or loneliness.…”
Section: Negative Emotionssupporting
confidence: 93%
“…Escaping or being chased as a dream topic during the COVID-19 pandemic has been investigated previously (Avci, 2022; Margherita et al, 2021). A qualitativ-quantitative study of 3,857 subjects’ dreams in Italy identified “escape from threat” as a main theme (Margherita et al, 2021), while another study of Chinese older people’s dreams during the pandemic also noted “being chased or pursued” as one of the reported themes (Yang et al, 2023). Many people in the pandemic were forced to keep social distance and quarantine once infected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations